A rare case of dicephalic parapagus conjoined twins - N’Guessan, Edouard; N’Guessan, Roseline Kouame; Gbeli, Franck; Guie, Privat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Dicephalic parapagus are one of the rare forms of conjoined twins. Their prognosis is usually very poor. Early prenatal diagnosis of these serious congenital abnormalities remains a real challenge for health systems in the low-income countries. The late antenatal diagnosis of a case of this abnormality was presented. The diagnosis was made at the 33rd week on the only ultrasound performed during the pregnancy. The pregnancy was interrupted with the agreement of the couple and delivery was performed by caesarean section.